Špecifiká marketingu a marketingovej komunikácie elektronických médií na Slovensku - Čábyová, Ľudmila (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2012)
The article presents characteristic features of marketing activities in the electronic media. After the initial description of the Slovak mass media, the author focuses on the media market and its use of advertising and of particular marketing communication tools.